Windows 10 simplified - McFedries, Paul. (2015)
"Windows 10 Simplified is your absolute beginner's guide to the ins and outs of Windows. Fully updated to cover Windows 10, this highly visual guide covers all the new features in addition to the basics, giving you a one-stop resource for complete Windows 10 mastery. Every page features step-by-step screen shots and plain-English instructions that walk you through everything you need to know, no matter how new you are to Windows. You'll master the basics as you learn how to navigate the user interface, work with files, create user accounts, and practice using the tools that make Windows 10 the most efficient Windows upgrade yet. This guide gets you up to speed quickly, with step-by-step screen shots that help you follow along with the clear, patient instruction."--Publisher annotation.
Getting started with Windows -- Customizing Windows -- Surfing the Web -- Sending and receiving email -- Getting social with Windows -- Performing day-to-day tasks with apps -- Working with images -- Working with multimedia -- Editing documents -- Working with files -- Implementing security -- Maintaining Windows.
"Step-by-step instructions for easy learning"--Cover.
Includes index.
Keywords: Microsoft Windows (Computer file); Microsoft Windows (Computer file); Operating systems (Computers); Windows 10.; Operating systems (Computers); Windows (Computer programs); Handbooks and manuals